2012
DOI: 10.1016/j.compstruct.2012.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Bending effect on the risk for delamination at the reinforcement/matrix interface of 3D woven fabric composite using a shell-like RVE

Abstract: This paper presents a computational homogenisation-based technique for flexural effects in textile reinforced composite planar shells. An homogenisation procedure is used for the in-plane and the out-of-plane behaviour of three-dimensional woven composite shells taking the in-plane periodicity of the material into account while relaxing any periodicity tying in the thickness direction. Several types of damage (matrix or reinforcement cracking, delamination, ...) can appear in a composite material. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…However, this will not prevent the efficiency of the new enriched concept of interzone being demonstrated. Indeed, it will be shown that the new interzone concept allows the experimental or numerical tendancies already demonstrated in earlier papers to be retrieved [7,9,19,29]: qualitative results and conclusions obtained in a general way are a particularly useful method to demonstrate the efficiency of the interzone concept. For that, the following questions will be examined:…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, this will not prevent the efficiency of the new enriched concept of interzone being demonstrated. Indeed, it will be shown that the new interzone concept allows the experimental or numerical tendancies already demonstrated in earlier papers to be retrieved [7,9,19,29]: qualitative results and conclusions obtained in a general way are a particularly useful method to demonstrate the efficiency of the interzone concept. For that, the following questions will be examined:…”
Section: Introductionmentioning
confidence: 94%
“…The approach has been to show that previous experimental or numerical analyses [7,9,19,29] of the failure of woven composites under classic loading configurations, (tensile loading, bending) can be easily retrieved by using the interzone concept (Tables 1, 2, 3,4,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of design tools dedicated to woven composites [35] and domain decomposition techniques has been accompanied by an increasing use of FE techniques for the computation of 3D woven composites, see Ref. [36] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the tensile and shear moduli, the flexural rigidities can also be evaluated, which constitutes an original aspect; the bending behavior is equally important as shear, for instance in shape forming applications and even for the study of delamination [36]. From a numerical viewpoint, the developed algorithms can easily be implemented as they rely on a text file including all necessary input data (geometry of the structure and microscopic properties of the yarns in terms of their geometry and mechanical moduli).…”
Section: Introductionmentioning
confidence: 99%